2021
DOI: 10.4103/njcp.njcp_490_20
|View full text |Cite
|
Sign up to set email alerts
|

Obesity Affects Health-Related Quality of Life in Schools Functioning Among Adolescents in Southwest of Nigeria

Abstract: Background: The relationship between body mass index (BMI) and health-related quality of life (HRQoL) in adolescence is important but there is a dearth of this information among developing countries such as Nigeria. To assess the relationship between BMI and HRQoL among healthy schooling adolescents in Southwestern Nigeria. Aims: We assessed the relationship between BMI and HRQoL among healthy schooling adolescents in southwestern Nigeria. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…3 Although many people do not perceive obesity as a disease, a number of both clinical and general community-based studies have reported impairment of various life-quality aspects in overweight and obese adolescents, compared with their normal-weight peers. 47 However, other studies have not confirmed the impact of weight on the quality of life. 89 The conflicting findings call for an in-depth investigation of the effect obesity may have on HRQoL in childhood and adolescence.…”
Section: Introductionmentioning
confidence: 99%
“…3 Although many people do not perceive obesity as a disease, a number of both clinical and general community-based studies have reported impairment of various life-quality aspects in overweight and obese adolescents, compared with their normal-weight peers. 47 However, other studies have not confirmed the impact of weight on the quality of life. 89 The conflicting findings call for an in-depth investigation of the effect obesity may have on HRQoL in childhood and adolescence.…”
Section: Introductionmentioning
confidence: 99%